2007
DOI: 10.1093/deafed/enm034
|View full text |Cite
|
Sign up to set email alerts
|

Text Communication Preferences of Deaf People in the United Kingdom

Abstract: This study is the only comprehensive survey to date of the text communication preferences of deaf people who cannot or prefer not to use voice telephony in the United Kingdom. Respondents covered a wide age range, became deaf or hard of hearing at different ages, and had different communication preferences. Generally, respondents used several forms of text communication, selecting them for particular purposes. E-mail was the most widely used form of text communication, but SMS was the most used by younger resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 3 publications
1
41
0
Order By: Relevance
“…E-Mail has the advantages that attachments and unlimited text length are possible [12]. Users are still constrained due to the asynchronous nature of the communication process.…”
Section: E-mailmentioning
confidence: 99%
See 1 more Smart Citation
“…E-Mail has the advantages that attachments and unlimited text length are possible [12]. Users are still constrained due to the asynchronous nature of the communication process.…”
Section: E-mailmentioning
confidence: 99%
“…The fax machine is still widely used (but not as the preferred means of communication) by deaf individuals, despite the fact that the technology is asynchronous, unsuitable for emergency communications and prone to occasional transmission difficulties [12]. "Fax machines are used for instrumental and informational purposes in that Deaf organisations use them to broadcast information to their members" [14].…”
Section: Faxmentioning
confidence: 99%
“…In investigating text communication preferences of deaf people in the United Kingdom Pilling and Barrett (2007) found that learning about the technology available and how to use it was a major problem in gaining access and that, "Older respondents were more likely to give …”
Section: Communicating With Deaf People About Communication Technologymentioning
confidence: 99%
“…For no group it is more true than that of deaf people. The development of radio and television excluded deaf people from an activity that has become everyday and essential for most people (Pilling & Barret, 2007). Unlike the hearing first and second language readers, deaf readers are not able to listen to the radio, and for only five minutes each day is there signed news on Swedish television.…”
Section: Written Texts Are Demandingmentioning
confidence: 99%